Acute Effects of Whole Egg Consumption on Circulating MicroRNAs in Sprague Dawley Animals (P15-001-19). (13th June 2019) - Bries, Amanda; Webb, Joe; Curry, Paige; Fischer, Savina; McNeill, Elizabeth; Clark, Stephanie; Rowling, Matthew; Schalinske, Kevin
Abstract: Objectives: MicroRNAs, small ∼22 nt non-coding RNAs, have a functional role in post-transcriptional regulation of gene expression. We have shown that whole egg-based diets reduce weight gain despite increased food intake compared to casein-based diets in Zucker-Diabetic Fatty (ZDF) rats. We hypothesized that the microRNA content of whole egg may underlie the differential impact on weight gain in ZDF rats. Our first objective was to characterize the circulating microRNA content in response to feeding whole egg-based diets over an 8 hour period. Our second objective was to identify and characterize the microRNAs present in whole egg- and casein-based diets. Methods: Male Sprague Dawley rats ( n  = 12; 6 weeks of age) were meal-trained to consume 4 grams of feed in one hour. After one week of meal-training, animals were fasted overnight for 10 hours (h) with water ad libitum followed by controlled feeding of either an AIN93G casein-based diet or isocaloric AIN93G diet containing whole egg (20% egg protein, w/w). At 8 weeks of age, serum was collected via the tail vein at 0, 2, 4, 6, and 8 h following refeeding. Serum microRNA was extracted using a RNA SPLIT kit and prepared for sequencing on an Illumina HiSeq 3000 using a smallRNA Library Prep. Five RNA extraction methods were tested on 6 samples of each diet: 1) Trizol (Invitrogen), 2) Trizol + Directzol (Zymogen), 3) Trizol followed by a second extraction using a fatty acid RNA extraction kit (Norgen), 4) mirPremier (Sigma-Aldrich), 5) ISOLATE II RNA (Bioline). RNA 260/280 ratios were assessed via Nanodrop and RNA integrity was assessed on an Agilent Bioanalyzer. Results: The greatest total RNA recovery (ng/µL) and most accurate 260/280 absorbance ratios were achieved using Trizol. The following concentrations of extracted RNA and their respective ratios (means ± SD) were achieved for each dietary component: casein diet (460.9 ± 528.1; 1.56 ± 0.12) and whole egg diet (394.3 ± 292.8; 1.55 ± 0.16), whole egg (73.4 ± 20.3; 1.15 ± 0.23), corn oil (67.5 ± 20.0; 1.41 ± 0.04), and cornstarch (247.12 ± 110.34; 1.64 ± 0.13). Total RNA recovered from the diets had an RNA integrity number (RIN) of 0 and microRNA concentrations were undetected. Conclusions: Despite successful total RNA recovery from the diets, all samples had a RIN value of 0, which is not optimal for downstream sequencing. Currently, microRNAs from plasma are being sequenced to determine if varying diets had differential effects on circulating microRNA expression. Funding Sources: Presidential Interdisciplinary Research Seed Grant Program, Iowa State University.